Does gender equality work for sustainable development in MENA?. (4th September 2019) - Karoui, Khayria; Feki, Rochdi
In recent years, MENA need gender equality and economic growth to ensure the economic well-being and to improve the living conditions of the population. This work focuses on the basis of the Kuznets curve associated with the analysis of the environment and aims to analyse the relationship between gender equality and sustainable development in the MENA region. In this work, a cross-analysis with data from 20 MENA regions that were used in 2010. The results find shows that there is a positive correlation between gender equality and sustainable development. When the multidimensional poverty index increases, reduce environmental problems, which brings us in the role of gender in sustainable development in all countries in MENA.